Potential For Night Culinary Tourism On Jalan Pekalipan Cirebon - Wibowo, Riyanto; Listiaty, Tia (Ann Publisher, 2024)
Research has been carried out on the culinary potential of mala m on Jalan Pekalipan Cirebon. The method used is a descriptive method by conducting surveys, interviews and secondary data analysis from various sources that can be accounted for. The results of the research indicate that Pekalipan culinary tourism located on Pekalipan street is the first culinary tourism carried out by the Cirebon City Government. Pekalipan Culinary Tourism was inaugurated as one of the culinary destinations through the Pekalipan Festival activities, which was inaugurated on Saturday, September 22, 2022, Pekalipan Culinary Tourism: The first culinary tour in the city of Cirebon initiated by the Cirebon City Government. Pekalipan culinary tourism has 15 traders, each with culinary specialties served to visitors, both Cirebon specialties and contemporary foods. Pekalipan culinary tourism has been used as a tourism destination that can be developed by the city government by referring to the aspects that must be fulfilled as a tourism destination by looking at the 4 A aspects, namely attraction (attraction), accessible (system achieved), amenities (facilities) and ancillary (tourism institutions). Pekalipan Culinary Tourism, as one of the culinary tourism in Cirebon City, can be developed as one of the attractions in the city of Cirebon as a tourism destination, but the following steps must be taken: There is a close cooperative relationship with various nearby tourist objects such as the Kacirebonan palace, Kasepuhan palace, and Kanoman palace to attract visitors to Pekalipan culinary tourism. There must be improvements and additions of facilities that visitors can use and utilize, such as toilets, safe and comfortable parking lots, and entertainment art and culture typical of Cirebon so that visitors will feel more typical of the city of Cirebon. The formation of forums in the form of Pekalipan culinary tourism institutions to form activities to attract tourists to visit Pekalipan culinary tourism.